The Lost Penalties: Critical Tangle about Ecuador’s Prison System - da Fonte Carvalho, Marcella (2022)
The extreme violence experienced in the prisons of Ecuador claimed 79 lives in February 2021. The article proposes an approach to the facts from three axes: the function of the penalty, the international obligations of the Ecuadorian State in terms of Human Rights and criminal policy. The analysis takes into account the national and international regulations on the matter, the jurisprudence of the Inter-American Court, as well as reference authors. It is concluded that the conditions of imprisonment in Ecuador are incompatible with the human rights of persons deprived of liberty and with the constitutional purposes of the penalty. Likewise, the prison issue is analyzed from criminal policy, understood as public policy according to inter-American standards.